Assessment of Useful Plants in the Catchment Area of the Proposed Ntabelanga Dam in the Eastern Cape Province, South Africa - Alfred Maroyi (The Scientific World Journal)
Background. The developmental projects, particularly construction of dams, result in permanent changes of terrestrial ecosystems through inundation. Objective. The present study was undertaken aiming at documenting useful plant species in Ntabelanga dam catchment area that will be impacted by the construction of the proposed dam. Methods. A total of 55 randomly selected quadrats were used to assess plant species diversity and composition. Participatory rural appraisal (PRA) methods were used to identify useful plant species growing in the catchment area through interviews with 108 randomly selected participants. Results. A total of 197 plant species were recorded with 95 species (48.2%) utilized for various purposes. Use categories included ethnoveterinary and herbal medicines (46 species), food plants (37 species), construction timber and thatching (14 species), firewood (five species), browse, live fence, and ornamental (four species each), and brooms and crafts (two species). Conclusion. This study showed that plant species play an important role in the daily life and culture of local people. The construction of Ntabelanga dam is, therefore, associated with several positive and negative impacts on plant resources which are not fully integrated into current decision-making, largely because of lack of multistakeholder dialogue on the socioeconomic issues of such an important project.